Effects of a Newly Developed Therapeutic Deep Heating Device Using High Frequency in Patients with Shoulder Pain and Disability: A Pilot Study - Gi-Wook Kim; Yu Hui Won; Sung-Hee Park; Jeong-Hwan Seo; Dae-hyun Kim; Hyung Nam Lee; Myoung-Hwan Ko (Pain Research and Management)
Objectives. The newly developed therapeutic deep heating device can generate deep heat in focal tissue using high-frequency wave stimulation. The objective of this study was to evaluate and compare the effectiveness of this deep heating device (HIPER-500®) with ultrasound in alleviating pain and improving function in patients with shoulder disability. Methods. This noninferiority trial was designed to compare the treatment effect of HIPER-500® to that of SonoStim® (ultrasound) on shoulder pain and disability. Thirty-eight patients with shoulder problems were assigned to either the HIPER-500® or SonoStim® group, and each participated in 10 min therapy sessions, five days a week for two weeks (for a total of ten sessions). Shoulder pain and disability were evaluated using the Visual Analogue Scale (VAS), the University of California at Los Angeles score (UCLA score), the Shoulder Pain and Disability Index (SPADI), and the Constant score in both groups before, immediately after, and four weeks after treatment. Statistical analysis was performed to compare the effects of treatment within and between the groups. Results. A total of 34 patients completed the study. The 18 patients in the HIPER-500® group and 16 patients in the SonoStim® group all showed significant improvements in shoulder pain and function when comparing pretreatment values with the results immediately after treatment and four weeks later. The results before and after treatment did not show a statistically significant difference between the two groups. Conclusions. The newly developed HIPER-500® for high-frequency deep heat therapy showed similar effects to those of SonoStim® for relieving pain and improving physical performance in the patients of this study. HIPER-500® may be a useful modality for treating shoulder pain and improving physical activity in patients with shoulder disease.